Politeness Strategies Found in Classroom Interaction Post-Graduate Student - Silfia Helmi (Rumah Jurnal UIN Bukittinggi, 2022)
The science of speech and context is known as pragmatics. Politeness strategy is one of many linguistic concerns covered in this study. There are four categories of politeness in the research on polite discourse that Brown and Levinson pioneered. Being polite seeks to lessen uncomfortable or unwelcome reactions. Culture and politeness can be related through research. The Minangkabau people believe that the use of the